Latent infections, coronavirus disease 2019 and psychiatric disorders: The friend of my enemy. Issue 4 (13th October 2022) - Mofazzal Jahromi, Mirza Ali; Sefidfard, Mina; Taghipour, Ali; Roustazadeh, Abazar; Matin, Sara; Mir, Hamed; Badri, Milad; Bahrami, Fares; Abdoli, Amir
Abstract: Recent reports revealed an increased rate of hospitalization and mortality of coronavirus disease 2019 (COVID‐19) among patients with psychiatric disorders. On the other hand, there is a link between latent infections, including Toxoplasma gondii, herpes simplex virus type 1 (HSV‐1) and cytomegalovirus (CMV) with psychiatric disorders. We individually assessed data regarding 1) the mortality rate of COVID‐19 among individuals with psychiatric disorders; 2) the association of latent infections in COVID‐19 patients and 3) the association between latent infections and psychiatric disorders. We developed the hypothesis that latent infection could increase the risk of severe COVID‐19 among patients with psychiatric disorders. Cumulative evidence proposed that infection with toxoplasmosis, CMV and HSV‐1 could increase the risk of severe acute respiratory syndrome coronavirus 2 (SARS‐Co‐V2) infections among patients with psychiatric disorders probably by induction of hyperinflammatory conditions. These infections are also associated with hyperinflammation and T cell exhaustion, which has also been observed in both schizophrenia and COVID‐19. This hypothesis provides new insights into the role of latent infections in increasing the mortality rates of COVID‐19 among individuals with psychiatric disorders. Strategies for screening, early diagnosis and treatment of these infections could be recommended for COVID‐19 patients with a background of psychiatric disorders.